Socioeconomic Inequalities in Chronic Liver Diseases and Cirrhosis Mortality in European Urban Areas before and after the Onset of the 2008 Economic Recession - Borrell, Carme; Palència, Laia; Bosakova, Lucia; Gotsens, Mercè; Morrison, Joana; Costa, Claudia; Dzurova, Dagmar; Deboosere, Patrick; Lustigova, Michala; Marí-Dell'Olmo, Marc; Rodopoulou, Sophia; Santana, Paula (International journal of environmental research and public health, 2021)
OBJECTIVE: To analyse the trends in chronic liver diseases and cirrhosis mortality, and the associated socioeconomic inequalities, in nine European cities and urban areas before and after the onset of the 2008 financial crisis. METHODS: This is an ecological study of trends in three periods of time: two before (2000-2003 and 2004-2008), and one after (2009-2014) the onset of the economic crisis. The units of analysis were the geographical areas of nine cities or urban areas in Europe. We analysed chronic liver diseases and cirrhosis standardised mortality ratios, smoothing them with a hierarchical Bayesian model by each city, area, and sex. An ecological regression model was fitted to analyse the trends in socioeconomic inequalities, and included the socioeconomic deprivation index, the period, and their interaction. RESULTS: In general, chronic liver diseases and cirrhosis mortality rates were higher in men than in women. These rates decreased in all cities during the financial crisis, except among men in Athens (rates increased from 8.50 per 100,000 inhabitants during the second period to 9.42 during the third). Socioeconomic inequalities in chronic liver diseases and cirrhosis mortality were found in six cities/metropolitan areas among men, and in four among women. Finally, in the periods studied, such inequalities did not significantly change. However, among men they increased in Turin and Barcelona and among women, several cities had lower inequalities in the third period. CONCLUSIONS: There are geographical socioeconomic inequalities in chronic liver diseases and cirrhosis mortality, mainly among men, that did not change during the 2008 financial crisis. These results should be monitored in the long term.
Keywords: urban areas; mortalita; Humans; chronic liver diseases; jaterní cirhóza; socioekonomické faktory; Female; Spain; lidé; financial crisis; Liver Cirrhosis; liver cirrhosis; Health Status Disparities; ekonomická recese; Španělsko; Mortality; Socioeconomic Factors; Economic Recession; Cities; ženské pohlaví; mortality; Male; Bayesova věta; disparity zdravotního stavu; mužské pohlaví; velkoměsta; Bayes Theorem; inequalities